2016
DOI: 10.32468/be.942
|View full text |Cite
|
Sign up to set email alerts
|

When bubble meets bubble : contagion in OECD countries

Abstract: We study the existence and international migration of housing market bubbles, using quarterly information of twenty OECD countries for the period comprised between 1970 and 2015. We find that housing bubbles are present in all the countries included in our sample. Multiple bubbles are found in all but two of those countries. We find ten episodes of migration. All of them had origin in the US housing bubble preceding the subprime crisis. Most migrations were to European countries. Notably, the Spanish housing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 22 publications
0
18
0
1
Order By: Relevance
“…The New South Wales government has adopted this view of planning policy noting that "[n]ew tools for rezoning will... unblock housing and employment supply" (NSW Government, 2013), while the Australian government established a National Housing Supply Council (NHSC) in 2008 to focus on "planning and development approval arrangements" to solve a "deficiency in supply [that] has contributed to rising house prices" NHSC (2013). But such policies never seem able to stop rapid home price growth, even in cities and countries widely claimed to have supply-friendly planning regulations (Costello & Rowley, 2010;Gurran & Phibbs, 2013;Gomez-Gonzalez et al , 2018). For example, Houston, Texas, is widely known for its unrestrictive zoning and responsive supply yet home prices increased 49% from 2012 to 2018 (U.S. Federal Housing Finance Agency, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The New South Wales government has adopted this view of planning policy noting that "[n]ew tools for rezoning will... unblock housing and employment supply" (NSW Government, 2013), while the Australian government established a National Housing Supply Council (NHSC) in 2008 to focus on "planning and development approval arrangements" to solve a "deficiency in supply [that] has contributed to rising house prices" NHSC (2013). But such policies never seem able to stop rapid home price growth, even in cities and countries widely claimed to have supply-friendly planning regulations (Costello & Rowley, 2010;Gurran & Phibbs, 2013;Gomez-Gonzalez et al , 2018). For example, Houston, Texas, is widely known for its unrestrictive zoning and responsive supply yet home prices increased 49% from 2012 to 2018 (U.S. Federal Housing Finance Agency, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…We collect quarterly data on all the included variables. Given that our emphasis is not in detecting housing bubbles but rather in finding the determinants of their duration, we take as given those bubbles encountered by Pavlidis et al () and Gomez‐Gonzalez et al () for a set of OECD countries. Both follow the recently developed bubble detection method of Phillips and Yu () and Phillips, Shi, and Yu ().…”
Section: Methods and Datamentioning
confidence: 99%
“…Papers studying housing bubble formation have shown that there is vast heterogeneity in their duration (Gomez‐Gonzalez, Gamboa‐Arbeláez, Hirs‐Garzón, & Pinchao‐Rosero, ; Pavlidis et al, ). Importantly, they show that bubbles occurring around the recent international financial crisis lasted significantly longer than did those that originated in the 1980s and 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…But such policies never seem able to stop rapid home price growth, even in cities and countries widely claimed to have supply-friendly planning regulations (Costello & Rowley, 2010;Gurran & Phibbs, 2013;Gomez-Gonzalez et al , 2018). For example, Houston, Texas, is widely known for its unrestrictive zoning and responsive supply yet home prices increased 49% from 2012 to 2018 (U.S. Federal Housing Finance Agency, 2019).…”
Section: Introductionmentioning
confidence: 99%